MODERASI CORPORATE GOVERNANCE PADA HUBUNGAN EARNINGS MANAGEMENT DAN KINERJA KEUANGAN - Putra, I Gede Cahyadi; Gunadi, I Gusti Ngurah Bagus (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2018)
The purpose of this study is to test and obtain empirical evidence of influence earnings management on firm performance and corporate governance influence on earnings management relationships and firm performance. The sample in this research is 40. The analysis tool used is Moderate Regression Analysis (MRA). Based on the results of the analysis can be concluded that earnings management has a positive effect on company performance. Corporate governance has no effect on the relationship between earnings management and firm performance.